Skin conditions of dogs presented to University Veterinary Hospital, Jan-Dec 2014 - Hasim, Norehan (2015)
A retrospective study was conducted to determine the prevalence of dermatological conditions in dogs presented to University of Veterinary Hospital (UVH), Faculty of Veterinary Medicine, Universiti Putra Malaysia, including the clinical manifestations, depth of investigation performed, and the risk factors for the most common skin conditions encountered. Of 1827 dogs presented to UVH from January 1st to December 31st 2014, 615 dogs were presented with dermatological problems, resulting in a prevalence of 33.66%. Erythema (15.99%) was the most common presenting clinical sign, followed by alopecia (13.38%), pruritus (12.88%), maculo-papular-pustular eruptions (11.01%) and scaling (9.33%). The five most common final diagnoses in descending order were malasseziasis, dermatophytosis, otitis externa, neoplasia and cutaneous myiasis. The acetate tape test (32.24%) was the most common diagnostic procedure performed, followed by trichograms (20.39%) and skin scrapes (13.93%). In dogs with malasseziasis, there was no association with age, sex, neuter status nor body condition score (BCS). However, dermatophytosis was significantly associated with the age where older dogs above 6 years of age had a 70% lower risk to have the disease compared to younger dogs. Otitis externa was significantly associated with the age, sex and BCS where females had as 50% lower risk compared to males, and the relative risk was nearly twice in obese and older dogs compared to the others. The top five breeds that were presented for dermatological conditions were mixed breed dogs, Shih Tzus, German Shepherds, Poodles and Cocker Spaniels.